Ethylene activation of carotenoid biosynthesis by a novel transcription factor CsERF061. (5th February 2021) - Zhu, Kaijie; Sun, Quan; Chen, Hongyan; Mei, Xuehan; Lu, Suwen; Ye, Junli; Chai, Lijun; Xu, Qiang; Deng, Xiuxin
Abstract : A novel transcription factor CsERF061, induced by ethylene, enhances carotenoid accumulation in citrus by directly regulating a series of carotenoid pathway genes during fruit ripening. Abstract: Chromoplast-specific lycopene β-cyclase (LCYb2) is a critical carotenogenic enzyme, which controls the massive accumulation of downstream carotenoids, especially provitamin A carotenoids, in citrus. Its regulatory metabolism is largely unknown. Here, we identified a group I ethylene response factor, CsERF061, in citrus by yeast one-hybrid screen with the promoter of LCYb2 . The expression of CsERF061 was induced by ethylene. Transcript and protein levels of CsERF061 were increased during fruit development and coloration. CsERF061 is a nucleus-localized transcriptional activator, which directly binds to the promoter of LCYb2 and activates its expression. Overexpression of CsERF061 in citrus calli and tomato fruits enhanced carotenoid accumulation by increasing the expression of key carotenoid pathway genes, and increased the number of chromoplasts needed to sequester the elevated concentrations of carotenoids, which was accompanied by changes in the concentrations of abscisic acid and gibberellin. Electrophoretic mobility shift and dual-luciferase assays verified that CsERF061 activates the promoters of nine other key carotenoid pathway genes, PSY1, PDS, CRTISO, LCYb1, BCH, ZEP, NCED3, CCD1, and CCD4, revealing the multitargeted regulation of CsERF061. Collectively, our findings decipher a novel regulatory network of carotenoid enhancement by CsERF061, induced by ethylene, which will be useful for manipulating carotenoid accumulation in citrus and other plants.